Stay Cool Why Dark Comedy Matters in the Fight Against Climate Change - Sachs, Aaron 1969- (New York University Press, 2023)
How gallows humor can bolster us to confront global warmingWe've all seen the headlines: oceans rising, historic heat waves, mass extinctions, climate refugees. It feels overwhelming, like nothing can make a difference in combating this ongoing global catastrophe. How can we mobilize to save the world when we feel this depressed? Stay Cool enjoins us to laugh our way forward. Human beings have used comedy to cope with difficult realities since the beginning of recorded time-the more dismal the news, the darker the humor. Using this rich tradition of dark comedy to investigate climate change, Aaron Sachs makes the case that gallows humor, a mainstay of African Americans and Jews facing extraordinary oppression, can cultivate endurance, persistence, and solidarity in the face of calamity. Sachs surveys the macabre tradition of laughing during great suffering, from the Black Plague to the San Francisco earthquake of 1906-and offers some of the earliest examples of superlative dark comedy. He also explores how a new generation of activists and comedians are deploying dark humor to great effect, by poking fun at older people's apathy about climate catastrophes, lambasting oil corporations' "eco" rebranding, and even producing an off-Broadway dystopian comedy called "Sea Level Rise." Sachs offers suggestions for how environmentalists can use dark comedy first to boost their own morale, and then to reframe their activism in more energizing and relatable ways. Environmentalism is probably the least funny social movement that's ever existed. Stay Cool seeks to change that. Will comedy save the world? Not by itself, no. But it can put people in a decent enough mood to get them started on a rescue mission